Risk Factors for Stunting in Children under the Age of 5 in Rural Guatemalan Highlands - Emily A. Kragel (Ubiquity Press, 2020)
Background: Previously, a study conducted by UNICEF found that malnutrition affects approximately 80% of the indigenous children in Guatemala. Objective: Identify prevalence and risk factors for stunted growth in communities surrounding Lake Atitlán, Guatemala. Methods: Height-for-age measurements of children under the age of five, N = 84, determined stunting prevalence and presumed burden of malnutrition in this region of the Guatemalan highlands. Mothers of a subset of this sample, N = 29, were interviewed to assess factors contributing to stunting. Analysis assessed the following risk factors: inadequate nutrition, increased infectious disease risk, high rate self-report illness, inadequate breastfeeding, and inadequate utilization of prenatal care. Findings: The majority of children under the age of five were stunted (65.6%) and likely malnourished. ANOVA analysis showed significant differences in mean height-for-age Z scores (HAZs) between groups with and without adequate nutrition (F = 7.069, p = 0.013), as well has with and without high rates of self-report illness (F = 6.894, p = 0.014). Both groups with inadequate nutrition (mean HAZs = –2.9, 95% CI = [–3.58, –2.24]) and high rates of self-report illness (mean HAZs = –2.8, 95% CI = [–3.13, –2.38]) had mean HAZs that are indicative of stunting. No other risk factors were associated with stunting. Conclusion: These pilot study results offer methods by which to obtain baseline data for assessing nutritional and public health interventions to improve stunting and malnutrition status as well as the health outcomes of children in rural, indigenous communities.